Inequalities in Energy Transition: The Case of Network Charges in Germany - Schlesewsky, Lisa; Winter, Simon (International Journal of Energy Economics and Policy, 2018)
The German energy transition and the rising share of renewable energies in electricity generation have led to an increase in network costs and to higher network charges in recent years. We use socioeconomic data in order to investigate distributional effects within the period 2010-2016, and employ three different inequality metrics – the Gini coefficient, the Theil index and the Atkinson index – all of which unambiguously indicate regressive effects of network charges. Most recently, the three metrics show an increase of economic inequality of at least 0.67 % when accounting for network charges. This finding is due to 1. the relative inferiority of electricity, 2. the regressive impact of a fixed component of network charges, 3. considerable regional disparities, and 4. the higher prevalence of prosumers within high-income households. Keywords: network charges, renewable energies, economic inequality JEL Classifications: D63, Q40, Q42 DOI: https://doi.org/10.32479/ijeep.6917